EMPLOYERS BAITUL ARQAM PROGRAM EVALUATION IN MUHAMMADIYAH UNIVERSITY of PALANGKARAYA - Nurul Hikmah Kartini (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
Muhammadiyah University of Palangkaraya is conducting certain members recruitment program for its employers on every Ramadhan, which is called Baitul Arqam. Issue found in this institution is that not all employers comprehend what is Al Islam and the Muhammadiyah-ism to be implemented in everyday life and worship. This Baitul Arqam program is one of implemented solution as the answer. As the program has been conducted for more than 3 (three) years, evaluation is necessary. This evaluation aims to identify Employers Baitul Arqam Program in Muhammadiyah University of Palangkaraya effectivity. This study applies CIPP evaluation model. CIPP evaluation model created by Stufflebeam focuses on four aspects, ie.: context, input, process, and product. Data sampling is performed through interviews, observations, and documentation. Study subjects as human information resources are University Chancellor, 1st Vice Chancellor, 2nd Vice Chancellor, Islamic Muhammadiyah-ism Development Institution (LPPKK) Director, Trainers, and Trainees/ employers in Muhammadiyah University of Palangkaraya, by taking samples of 80 individuals. Evaluation categorizations are divided into five ratings: Very Good, Good, Fair, Bad, and Very Bad. Evaluation result shows that: 1) Program requirements as well as its purposes and targets analysis regarding context component is categorized as very good.; 2) Planning strategy which includes material, human resources, means and infrastructure, fund, and learning method regarding inputs component in the BBTHA program in Muhammadiyah University of Palangkaraya is categorized as good; 3) In term of process component executed on the Employers Baitul Arqam program is categorized as good; 4) In term of product as the result of Employers Baitul Arqam program is categorized as good. The conclusion is, this Program can be proceed forward followed by some improvements.